Sex,marital status and family setting variables on inner meaning fulfillment among students of the University of Ibadan (2007)
The present study examined the influence of sex, marital status and family setting variables on Inner Meaning Fulfilment (IMF) on the students of the University of Ibadan. There were eight hundred and eighty five (885) with four hundred and forty nine (449) or 50% males and four hundred and thirty six (436) or 49.3% females. The mean age for the participants was 26.2 years with a standard deviation of 6.0 and age ranged from 15 to 60 years. The IMF Scale (Logotest),which is inform of a questionnaire format, was used for the data collection as a survey/Ex post-facto design were used with randomly selected students within University community. A two independent group sample test statistics was utilized to analyse the data. While two of the three. hypotheses stated were confirmed (Sex, t (871) =1.70.3, P< 0.05 and Family Setting = t (729) = 2.431. P<0.05 the third hypothesis on marital status t = 882 = 3.517 P<0.05was not confirmed. based on these findings there is an urgent need for early psychological screening/ assessment for the new student and provision of Special Counselling Services for all students especially those from polygamous setting, married student and female students. Implications and other recommendations were highlighted and discussed for relevance, in policy and planning for the Universities and other tertiary institutions.